Promising candidates from drug clinical trials: Implications for clinical treatment of Alzheimer's disease in China - Cao, Yuxia; Yu, Feng; Lyu, Yi; Lu, Xianfu (Frontiers in Neurology, 2022)
Alzheimer's disease is the most common neurodegenerative disease. Prior to 2017, National Medical Products Administration approved only four drugs to treat Alzheimer's disease, including three cholinesterase inhibitors and one N-methyl-D-aspartate receptor antagonist. We queried ClinicalTrials.gov to better understand Alzheimer's drug development over the past 5 years and found 16 promising candidates that have entered late-stage trials and analyzed their impact on clinical treatment of Alzheimer's disease in China. The 16 compounds selected include disease-modifying therapies and symptomatic therapies. The research and development pipeline now focuses on disease-modifying therapies such as gantenerumab, aducanumab, ALZ-801, ALZT-OP1, donanemab, lecanemab, simufilam, NE3107, semaglutide, and GV-971, which could put an end to the situation where Alzheimer's patients in China have no effective treatment alternatives. The reuse of drugs or combinations currently under investigation for the psychiatric treatment of Alzheimer's disease, including AXS-05, AVP-786, nabilone, brexpiprazole, methylphenidate, and pimavanserin, could provide physicians with additional treatment options. Although most of these drugs have not been explored in China yet, due to the current development trend in this field in China, it is expected that China will be involved in research on these drugs in the future.